2016
DOI: 10.20524/aog.2016.0112
|View full text |Cite
|
Sign up to set email alerts
|

High serum ferritin is associated with worse outcome of patients with decompensated cirrhosis

Abstract: BackgroundStudies in patients with decompensated cirrhosis showed a correlation between serum ferritin levels and patients’ prognosis. Besides, red blood cell distribution width (RDW) and mean platelet volume (MPV) have been associated with the severity of hepatic function. The aim of this study was to evaluate the prognostic impact of serum ferritin and RDW/MPV in the outcome [survival, death, or liver transplantation (LT)] of patients with stable decompensated cirrhosis.MethodsConsecutive adult patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…It is in line with research conducted by Olmes et al and Büyükaşik et al [3,13] Oikonomou et al showed that the best cut-off point for the outcome was ferritin >55 ng/ml with sensitivity 85.3% and specificity 11.2% and patients with ferritin > 55 had aworse outcome, compared to those with ferritin ≤ 55 ng/ml. [8] In this study, there was an increase in ferritin levels along with worsening of disease characterized by an increase in the Child-Pugh class.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…It is in line with research conducted by Olmes et al and Büyükaşik et al [3,13] Oikonomou et al showed that the best cut-off point for the outcome was ferritin >55 ng/ml with sensitivity 85.3% and specificity 11.2% and patients with ferritin > 55 had aworse outcome, compared to those with ferritin ≤ 55 ng/ml. [8] In this study, there was an increase in ferritin levels along with worsening of disease characterized by an increase in the Child-Pugh class.…”
Section: Discussionsupporting
confidence: 46%
“…Their lines of evidence suggest that iron may be an important co-factor in the progression of liver cirrhosis. [8] Ferritin synthesis is induced by macrophages, and hepatocytes and raised levels can be seen either in iron overload conditions or several pathologies, inflammation, infection and liver diseases. [9] Walker et al showed that serum ferritin could be an independent predictor of mortality in cirrhosis patients awaiting LT and high levels associated with the higher frequency of liver-related complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity of the findings across a broad spectrum of different chronic liver diseases and resolution of the abnormalities during treatment suggest that the disturbances are consequences of liver injury . Alternatively, the association of the iron disturbances with disease severity and the recognised hepatotoxicity of iron overload compel consideration of iron as a pathogenic factor.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperferritinemia is also an important prognostic marker that has been associated with dire outcomes in advanced chronic liver disease, and it may have a nefarious role in some forms of liver disease that counters its anti‐oxidant and cytoprotective actions. Ferritin can promote Fas‐mediated apoptosis, activate hepatic stellate cells (HSCs), increase hepatic fibrosis, and behave as a pro‐inflammatory cytokine (Table ) .…”
Section: Resultsmentioning
confidence: 99%